2017
DOI: 10.1038/s41598-017-13394-0
|View full text |Cite
|
Sign up to set email alerts
|

Experimental demonstration of magnetoplasmon polariton at InSb(InAs)/dielectric interface for terahertz sensor application

Abstract: We experimentally demonstrate surface plasmon resonance (SPR) in the terahertz range in InSb and InAs. The surface plasmon is excited on the interface between a thin polymer film and the semiconductor using a silicon prism in Otto configuration. The low effective mass of InSb and InAs permits tuning of the SPR by an external magnetic field in the transversal configuration. The data show a good agreement with a model. Strong excitation of the surface plasmon is present in both materials, with a shifting of reso… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
26
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 44 publications
(26 citation statements)
references
References 25 publications
0
26
0
Order By: Relevance
“…One of the advantages of THz SPWs on semiconductor surfaces is the active control of the doping level by temperature, optical pump, magnetic field, etc., which is promising in switching and tuning applications. [87][88][89][90][91] Savel'ev et al 92 predicted the existence of terahertz surface waves in layered superconductors below the Josephson plasma frequency ω j , and such waves are called surface Josephson plasma waves (SJPWs). In a semi-infinite sample, SJPWs can propagate along the interface between an external dielectric and a layered superconductor.…”
Section: Thz Spws On Doped Semiconductor Superconductor and Graphenmentioning
confidence: 99%
“…One of the advantages of THz SPWs on semiconductor surfaces is the active control of the doping level by temperature, optical pump, magnetic field, etc., which is promising in switching and tuning applications. [87][88][89][90][91] Savel'ev et al 92 predicted the existence of terahertz surface waves in layered superconductors below the Josephson plasma frequency ω j , and such waves are called surface Josephson plasma waves (SJPWs). In a semi-infinite sample, SJPWs can propagate along the interface between an external dielectric and a layered superconductor.…”
Section: Thz Spws On Doped Semiconductor Superconductor and Graphenmentioning
confidence: 99%
“…We consider doped Indium Antimonide (InSb) slab which has been most widely studied in the context of coupled magneto-plasmon surface polaritons [41,42] and whose material permittivity dispersion has been wellcharacterized experimentally [43][44][45][46]. For the sake of completeness of our study, we extend the known permittivity model in [44][45][46] to the case of an arbitrarily oriented magnetic field in our geometry and obtain the semi-analytic form of permittivity given by e e w w w where m e =9.109 4×10 −31 kg is electron mass.…”
Section: Practical Example Of Insb Slabmentioning
confidence: 99%
“…The transmission, polarization, and magnetooptical properties of InSb have been widely investigated in recent years. [31][32][33][34][35][36][37][38][39][40][41][42] For instance, in 2018, Lin et al [36] reported a nonreciprocal THz reflection on the InSb with the transverse magneto-optical effect (i.e., Voigt configuration). This one-way mirror achieves 35 dB isolation with 6.2 dB insertion loss for a certain linearly polarized (LP) state.…”
Section: Introductionmentioning
confidence: 99%